An Analysis of Process and Meaning of Ro’a Mu’u Ceremony in Pogon Village Waigete District Sikka Regency - Geor, Elisabeth Avianita; Nur Syamsiyah Eksan; Antonius M. K. Naro (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the process of Ro’a mu’u ceremony in Pogon village and also To Analyzing meaning of the Ro’a mu’u ceremony in Pogon village. The research used qualitative method and data collection techniques are, interview, and documentation. Data analysis in this research used data reduces, data display, and drawing conclusion. The result of this research showed that Ro'a Mu’u is a marriage ritual as a symbol of the second opportunity for the bride and groom.Ro'amu'u is performed at the bride's house, after the bride and groom carry out a church wedding. Ro'amu'u is carried out home from the church in accordance with the agreement of both parties, namely the male side (me pu) and the female side (inaama). In this process, the woman will plant a banana tree in front of the house and replace the traditional Sikka sarong, in general, ro’amu’u in Sikka district is one of the traditional ceremonies marriage that is prioritized in traditional wedding ceremonies, Meaning of ro'amu'u is that the bride and groom feel that marriage is a very sacred value with the aim of continuing offspring so that their marriage is symbolized by meaning and social values. specialy in Pogaon village must preserve the customs and culture of ro'a mu'u the younger generation because this ceremony is a sacred wedding ceremony with the aim of continuing the lineage so that the younger generation must learn and carry out this ceremony for generations.